Serum IL-23 levels reflect a myeloid inflammatory signature and predict the response to apremilast in patients with psoriatic arthritis - De Santis, Maria; Tonutti, Antonio; Isailovic, Natasa; Motta, Francesca; Rivara, Radu Marian; Ragusa, Rita; Guidelli, Giacomo M.; Caprioli, Marta; Ceribelli, Angela; Renna, Daniela; Luciano, Nicoletta; Selmi, Carlo (Frontiers in Immunology, 2024)
BackgroundThe phosphodiesterase 4 (PDE4) inhibitor apremilast downregulates the production of IL-23 and other pro-inflammatory cytokines involved in the pathogenesis of psoriatic arthritis (PsA).AimTo investigate the effects of apremilast on the production of cytokines by peripheral blood monocyte-derived macrophages, innate-like lymphocyte cells (ILCs), mucosal-associated invariant T (MAIT) cells, γδ T cells, natural killer (NK) cells, and NKT-like cells from patients with PsA manifesting different clinical responses to the treatment.MethodsPeripheral blood samples were obtained from patients with PsA at baseline and after 1 and 4 months of apremilast therapy (n = 23) and 20 controls with osteoarthritis. Cytokine expression in peripheral blood monocyte-derived macrophages and ILCs/MAIT/γδT/NK/NKT-like cells was tested by RT-PCR and FACS analyses, respectively; cytokine levels in culture supernatants and sera were analyzed by ELISA.ResultsPsA monocyte-derived macrophages exhibited higher expressions of IL-23, IL-1β, and TNF-α, compared with OA controls, more profoundly in patients responding to apremilast. There were 17/23 (74%) PsA patients who were classified as responders to apremilast at 4 months, and a baseline serum IL-23 >1.4 pg/mL was associated with the responder status (AUCROC 0.79; sensitivity 100%, specificity 68%). Of note, apremilast led to a significantly reduced expression of IL-23 in peripheral blood monocyte-derived macrophages; IL-17 in ILC1 and in T cells of responder patients; IFN-γ in γδ T lymphocytes.ConclusionAn enhanced myeloid inflammatory signature characterizes PsA monocyte-derived macrophages, and serum IL-23 levels represent candidate biomarkers for PsA response to apremilast.